IDENTIFIKASI TANTANGAN PADA PEMBELAJARAN DI SDN MITRA BAGI MAHASISWA PESERTA PROGRAM KAMPUS MENGAJAR CALON GURU IPA FKIP ULM - Pratiwi, Yessi Anissa; Sauqina; Sari, Mella Mutika (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2023)
Learning activities have changed in Indonesia as a result of the COVID-19 epidemic. One of them is the SDN Mitra education program. Thus, the purpose of this study was to determine the difficulties in implementing the teaching campus program at SDN Mitra for prospective science educators at FKIP ULM. School administrators, teachers, education personnel, students, and the community at SDN Mitra were the research subjects. An autoethnographic qualitative research approach was used in this study. using unstructured interviews, observation, and documentation as data collection methods. This writing shows that (1) in learning class III, students have skills in teaching, including teaching styles in the classroom, the use of tools when teaching, interaction patterns in teaching, students' ability to arouse curiosity, students' ability to achieve learning objectives, giving questions or oral, giving praise for the results achieved by students. (2) There are 4 grade III students who have difficulties such as reading, writing, and calculating difficulties, (3) In the use of technology at SDN Mitra, there are 2 educators who are not good at using technology. This is due to the age factor so that the ability to use technology is reduced.